DINAMIKA KONFLIK SOSIAL SISWA BARU DAN PERAN GURU DALAM MENGATASINYA : STUDI KASUS SISWA KELAS 7 DI SMP ZAMZAM INTEGRATED ISLAMIC SCHOOL - Kubro, Syaikhul; Muh. Hanif (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to examine the role of teachers in overcoming conflicts that occur in new students, especially grade 7 students at Zamzam Integrated Islamic School (ZIIS). Using a descriptive-qualitative approach, this study reveals various types of conflicts experienced by students, such as individual conflicts, between individuals, and between individuals and groups. Factors that trigger conflict include emotional immaturity and family background (broken home). The research shows that teachers play an important role as mediators, non-judgmental companions, teachers of problem-solving skills, and communicators between schools and parents. These strategies are strengthened by the synergy between teachers, the support of the principal, and the involvement of parents through the “parent teaching” program. The results confirm that effective conflict management contributes to the creation of a comfortable, conducive learning environment that supports students' character development. This study is expected to be a reference for other educational institutions in managing student conflicts constructively. Keywords: teacher role, conflict management, new students